Beam energy scaling of ion-induced electron yield from K^{+} impact on stainless steel - Michel Kireeff Covo; Arthur W. Molvik; Alex Friedman; Glen Westenskow; John J. Barnard; Ronald Cohen; Peter A. Seidl; Joe W. Kwan; Grant Logan; David Baca; Frank Bieniosek; Christine M. Celata; et al. (Physical Review Special Topics. Accelerators and Beams, 2006)
Electron clouds limit the performance of many major accelerators and storage rings. Significant quantities of electrons result when halo ions are lost to beam tubes, generating gas which can be ionized and ion-induced electrons that can multiply and accumulate, causing degradation or loss of the ion beam. In order to understand the physical mechanisms of ion-induced electron production, experiments studied the impact of 50 to 400 keV K^{+} ions on stainless steel surfaces near grazing incidence, using the 500 kV ion source test stand (STS-500) at LLNL. The experimental electron yield scales with the electronic component (dE_{e}/dx) of the stopping power and its angular dependence does not follow 1/cos⁡(θ). A theoretical model is developed, using TRIM code to evaluate dE_{e}/dx at several depths in the target, to estimate the electron yield, which is compared with the experimental results. The experiment extends the range of energy from previous works and the model reproduces the angular dependence and magnitude of the electron yield.